Influence of piston bowl geometry on combustion and emission characteristics - ÖZDEMİR, MEHMED RAFET; YANGAZ, MURAT UMUT; ŞENER, RAMAZAN (SAGE PUBLICATIONS LTD, 2019)
Together with the global energy concerns, the norms are getting stringent to prevent the emission threat. There are on-going studies on systems working with both fossil and renewable energy sources aiming to create more efficient and less emissive processes and devices. Accordingly, a set of numerical simulations was performed to examine the effect of the bowl shape of a piston on the performance behaviour, emission rates and combustion characteristics in a four-cylinder, four strokes, water-cooled compression ignition engine using n-heptane (C7H16) as fuel. Six different piston bowl geometries, five from the literature and proposed one, were utilized having different length-to-diameter ratio, curvature and sidewall radius. The study was conducted at 1750 r/min engine speed and a constant compression ratio with a full performance condition. The intake and exhaust valves have been considered as closed during the analysis to provide the variation of crank angle from 300 CA to 495 CA. The results showed that the piston bowl geometry has a significant impact on the rate of heat release, in-cylinder pressure, in-cylinder temperature, and emission trends in the engine. Among the piston bowl geometries studied, design DE and design DF exhibited better combustion characteristics and relatively lower emission trends compared to other designs. The observed rate of heat release, in-cylinder pressure and in-cylinder temperature magnitudes of these two geometries was higher in comparison to other geometries. Moreover, the trade-off for NOx emission was also observed higher for these piston bowl designs.
Keywords: Combustion; emissions; bowl design; CFD; internal combustion engine; DIESEL-ENGINE; CHAMBER GEOMETRY; OPERATING-CONDITIONS; METHYL-ESTER; PERFORMANCE; BIODIESEL; FUEL; OPTIMIZATION; SWIRL; RATIO